2017
DOI: 10.1136/jclinpath-2017-204475
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of intact and cleaved urokinase plasminogen activator receptor (uPAR) in men with clinically localised prostate cancer

Abstract: Addition of uPAR(I) level to known diagnostic parameters did not increase the prediction of N1 disease following RP in men with clinically localised PCa. Our results indicate that the plasma levels at diagnosis of the different uPAR forms do not hold important predictive or prognostic information in men with clinically localised PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Here, we found that intact and cleaved plasma uPAR levels were increased significantly in locally advanced or lymph node positive disease. This builds on the previous findings within the CuPCa database, showing that the uPAR system is more active in men with larger tumor burden [15]. We hypothesized that high levels of cleaved uPAR could have biomarker potential in localized PCa.…”
Section: Discussionsupporting
confidence: 73%
“…Here, we found that intact and cleaved plasma uPAR levels were increased significantly in locally advanced or lymph node positive disease. This builds on the previous findings within the CuPCa database, showing that the uPAR system is more active in men with larger tumor burden [15]. We hypothesized that high levels of cleaved uPAR could have biomarker potential in localized PCa.…”
Section: Discussionsupporting
confidence: 73%